Proteome Damage Inflicted by Ionizing Radiation: Advancing a Theme in the Research of Miroslav Radman - Steven T. Bruckbauer; Benjamin B. Minkoff; Michael R. Sussman; Michael M. Cox (Cells, 2021)
Oxidative proteome damage has been implicated as a major contributor to cell death and aging. Protein damage and aging has been a particular theme of the recent research of Miroslav Radman. However, the study of how cellular proteins are damaged by oxidative processes is still in its infancy. Here we examine oxidative changes in the proteomes of four bacterial populations—wild type E. coli, two isolates from E. coli populations evolved for high levels of ionizing radiation (IR) resistance, and D. radiodurans—immediately following exposure to 3000 Gy of ionizing radiation. By a substantial margin, the most prominent intracellular oxidation events involve hydroxylation of methionine residues. Significant but much less frequent are carbonylation events on tyrosine and dioxidation events on tryptophan. A few proteins are exquisitely sensitive to targeted oxidation events, notably the active site of glyceraldehyde 3-phosphate dehydrogenase (GAPDH) in E. coli. Extensive experimental evolution of E. coli for IR resistance has decreased overall proteome sensitivity to oxidation but not to the level seen in D. radiodurans. Many observed oxidation events may reflect aspects of protein structure and/or exposure of protein surfaces to water. Proteins such as GAPDH and possibly Ef-Tu may have an evolved sensitivity to oxidation by H2O2.